Prevalence of celiac disease in Indian patients with irritable bowel syndrome and uninvestigated dyspepsia. Issue 8 (10th September 2015) - Sharma, Hanish; Verma, Anil K; Das, Prasenjit; Dattagupta, Siddhartha; Ahuja, Vineet; Makharia, Govind K
<x xml:space="preserve">Abstract</x> Objective The clinical spectrum of celiac disease (CeD) is wide and its symptoms overlap with those of functional bowel diseases. This study aimed to investigate the relationship among gluten‐related disorders, irritable bowel syndrome (IBS) and uninvestigated dyspepsia in Indian patients. Methods Patients with IBS and uninvestigated dyspepsia (using Rome III criteria) were tested for immunoglobulin A (IgA) anti‐tissue transglutaminase (anti‐tTG) antibody and anti‐gliadin antibody (AGA). Those with positive anti‐tTG antibody were evaluated for the presence of villous abnormalities. Patients who were only IgA AGA‐positive were considered to have gluten sensitivity and those with positive anti‐tTG antibody and villous atrophy were considered to have CeD. Results Of 362 patients with IBS, 22 (6.1%) had positive anti‐tTG antibody, among whom 3 (0.8%) had CeD and 19 had potential CeD. Of 358 patients with uninvestigated dyspepsia, 18 (5.0%) were anti‐tTG antibody‐positive and among them 4 (1.1%) had CeD and 14 had potential CeD. AGA was positive in 104 (28.7%) patients with IBS and 68 (19.0%) with uninvestigated dyspepsia, suggesting the presence of gluten sensitivity. Conclusion This study highlights the relationship between IBS or dyspepsia and CeD or gluten sensitivity.